A novel conditional Sgsh knockout mouse model recapitulates phenotypic and neuropathic deficits of Sanfilippo syndrome. Issue 5 (27th April 2017) - Lau, Adeline A.; King, Barbara M.; Thorsen, Carly L.; Hassiotis, Sofia; Beard, Helen; Trim, Paul J.; Whyte, Lauren S.; Tamang, Sarah J.; Duplock, Stephen K.; Snel, Marten F.; Hopwood, John J.; Hemsley, Kim M.
Abstract: Mucopolysaccharidosis (MPS) type IIIA, or Sanfilippo syndrome, is a neurodegenerative lysosomal storage disorder caused by a deficiency of the lysosomal enzyme N ‐sulfoglucosamine sulfohydrolase (SGSH), involved in the catabolism of heparan sulfate. The clinical spectrum is broad and the age of symptom onset and the degree of preservation of cognitive and motor functions appears greatly influenced by genotype. To explore this further, we generated a conditional knockout ( Sgsh KO ) mouse model with ubiquitous Sgsh deletion, and compared the clinical and pathological phenotype with that of the spontaneous Sgsh D31N MPS‐IIIA mouse model. Phenotypic deficits were noted in Sgsh KO mice prior to Sgsh D31N mice, however these outcomes did not correlate with any shift in the time of appearance nor rate of accumulation of primary (heparan sulfate) or secondary substrates (GM2/GM3 gangliosides). Other disease lesions (elevations in lysosomal integral membrane protein‐II expression, reactive astrocytosis and appearance of ubiquitin‐positive inclusions) were also comparable between affected mouse strains. This suggests that gross substrate storage and these neuropathological markers are neither primary determinants, nor good biomarkers/indicators of symptom generation, confirming similar observations made recently in MPS‐IIIA patients. The Sgsh KO mouse will be a useful tool for elucidation of the neurological basis of disease and assessment of the clinical efficacy of new treatments for Sanfilippo syndrome.